2012
DOI: 10.1016/j.bodyim.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Pure versus guided mirror exposure to reduce body dissatisfaction: A preliminary study with university women

Abstract: While effectiveness of mirror exposure to reduce body dissatisfaction has been demonstrated, the exposure was almost always combined with other interventions. The aim of the study was to evaluate the effectiveness of a pure mirror exposure intervention compared with a guided mirror exposure (participants are guided to describe their body shape in a non-evaluative manner) and an imagery exposure intervention (participants are guided to describe their body through mental representation). Thirty-one women with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 9 publications
6
48
1
Order By: Relevance
“…The finding that a body scan negatively influences the implicit body image of overweight participants is not only in line with studies demonstrating that associations measured by the IAT are generally capable of being influenced by situational factors (Gawronski & Conrey, 2004), but also with studies showing that situations enforcing high attention to one's own appearance can have a negative impact on one's self-evaluation (Beach, 1993;Hoffmeister et al, 2010;Moreno-Domínguez et al, 2012;Windheim et al, 2011). It can be assumed that the increased self-focus, which is induced by the scanning procedure, leads to a comparison with implicit standards, which -in case of overweight people -turns out unsatisfactory and thereby has a negative impact on the body image of the user (Carver & Scheier, 1981).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The finding that a body scan negatively influences the implicit body image of overweight participants is not only in line with studies demonstrating that associations measured by the IAT are generally capable of being influenced by situational factors (Gawronski & Conrey, 2004), but also with studies showing that situations enforcing high attention to one's own appearance can have a negative impact on one's self-evaluation (Beach, 1993;Hoffmeister et al, 2010;Moreno-Domínguez et al, 2012;Windheim et al, 2011). It can be assumed that the increased self-focus, which is induced by the scanning procedure, leads to a comparison with implicit standards, which -in case of overweight people -turns out unsatisfactory and thereby has a negative impact on the body image of the user (Carver & Scheier, 1981).…”
Section: Discussionsupporting
confidence: 79%
“…This procedure was supposed to increase the salience of body shape and weight and led to a decrease of the implicit self-esteem of restrained eaters. In another study the mirror exposure led to a short-term increase in discomfort (Moreno-Domínguez et al, 2012). In addition, it has been shown that focusing on one's own face through mirror-gazing does not only lead to an increased self-focused attention but also to an increased distress in healthy participants (Windheim, et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…ÔpureÕ mirror exposure without any guidance has been found to improve body satisfaction in a non-clinical, female sample (Moreno-Dom'nguez, Rodr'guez-Ruiz, Fern ‡ndez-Santaella, Jansen, & Tuschen-Caffier, 2012). However, this later study did not examine the effect of such ÔpureÕ exposure in individuals with eating disorders or body image disturbance, and further research is needed to establish more clearly the effect of pure mirror exposure on body satisfaction in individuals with different body image disturbances or eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A different method of mirror exposure for the treatment of body dissatisfaction was recently proposed by Moreno-Domínguez, Rodríguez-Ruiz, Fern andez-Santaella, Jansen, and Tuschen-Caffier (2012). These authors examined, in a group of women with high body dissatisfaction, but without EBDs, whether pure exposure to one's own body would be effective in reducing body dissatisfaction compared with the guided exposure developed by Tuschen-Caffier and Florin (2002).…”
Section: Introductionmentioning
confidence: 97%